ANALISIS SISTEM JASA PENGEMBALIAN SPP PNPM-MP DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Azwar Hamid (Institut Agama Islam Negeri Padngsidimpuan, 2016)
PNPM-MP stands for Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan. This program deals with rural society development. In the other words, PNPM-MP supplies fund for physical or non-physical development finance. The physical developmental finance can be forn of farming, sidewind, lavatory, etc.The non-physical developmental finance is saving and loan cooperative especially for women only which is called SPP. The system of SPP (joint liability) in Islamic economic is known as kafalah.